ANALISIS STRUKTURAL NOVEL LUPAKAN PALERMO KARYA GAMA HARJONO DAN ADHITYA PATTISAHUSIWA - Septy Nurillah; Sesilia Seli; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract The main focus of the research is desire to describe the intrinsic elements contained in the novel Lupakan Palermo, and its implementation of Indonesian language learning at the high school level. The theoretical study used is related to structural, novel and intrinsic elements. The research method used is qualitative research with an objective approach. Data in the form of words, sentences, quotes. The data source is the novel Lupakan Palermo by Gama Harjono and Adhitya Pattisahusiwa. The data collection technique used is the documentary study technique. Data analysis techniques, namely, analyzing and interpreting the intrinsic elements in the form of themes, pathways, settings, characters and characterizations, points of view, and mandates, designing learning implementation plans, discussing the results of analysis, making conclusions. The results of this study are (1) intrinsic elements in the form of themes regarding commitment, dilemma, betrayal. Progressive / forward flow. The main character Reno, and 21 other figures are additional figures and characterizations. 36 place settings, 20 time settings, and 6 atmosphere settings. The point of view used by a third person is all-rounder. The mandate of honesty. (2) The design of the implementation of learning using novel texts in learning in SMA class XII. Keywords: structural, novel, intrinsic elements